Statement by the Kommission Ovar of the AGO: The New FIGO and WHO Classifications of Ovarian, Fallopian Tube and Primary Peritoneal Cancer - Meinhold-Heerlein, I.; Fotopoulou, C.; Harter, P.; Kurzeder, C.; Mustea, A.; Wimberger, P.; Hauptmann, S.; Sehouli, J.; for the Kommission Ovar of the AGO (Geburtshilfe und Frauenheilkunde, 2015)
More than 25 years after the last revision, in 2012 the FIGO Oncology Committee began revising the FIGO classification for staging ovarian, Fallopian tube and primary peritoneal cancers. The new classification has become effective with its publication at the beginning of 2014. Following recent findings on the pathogenesis of ovarian, Fallopian tube and primary peritoneal cancer and reflecting standard clinical practice, the three entities have now been classified uniformly. The histological subtype is included (high-grade serous – HGSC; low-grade serous – LGSC; mucinous – MC; clear cell – CCC; endometrioid – EC). Stages III and IV have been fundamentally changed: stage IIIA now refers to a localized tumor limited to the pelvis with (only) retroperitoneal lymph node metastasis (formerly classified as IIIC). Stage IV has been divided into IVA and IVB, with IVA defined as malignant pleural effusion and IVB as parenchymatous or extra-abdominal metastasis including inguinal and mediastinal lymph node metastasis as well as umbilical metastasis. A new WHO classification was published almost concurrently. The classification of serous tumors addresses the issue of the tubal carcinogenesis of serous ovarian cancer, even if no tubal precursor lesions are found for up to 30 % of serous high-grade cancers. The number of subgroups was reduced and subgroups now include only high-grade serous, low-grade serous, mucinous, seromucinous, endometrioid, clear cell and Brenner tumors. The category “transitional cell carcinomas” has been dropped and the classification “seromucinous tumors” has been newly added. More attention has been focused on the role of borderline tumors as a stage in the progression from benign to invasive lesions.
Keywords: borderline tumor; FIGO stage; ovarian cancer subtypes